An Intranuclear Sodalis-Like Symbiont and Spiroplasma Coinfect the Carrot Psyllid, Bactericera trigonica (Hemiptera, Psylloidea) - Saptarshi Ghosh; Noa Sela; Svetlana Kontsedalov; Galina Lebedev; Lee R. Haines; Murad Ghanim (Microorganisms, 2020)
Endosymbionts harbored inside insects play critical roles in the biology of their insect host and can influence the transmission of pathogens by insect vectors. Bactericera trigonica infests umbelliferous plants and transmits the bacterial plant pathogen Candidatus Liberibacter solanacearum (CLso), causing carrot yellows disease. To characterize the bacterial diversity of B. trigonica, as a first step, we used PCR-restriction fragment length polymorphism (PCR-RFLP) and denaturing gradient gel electrophoresis (DGGE) analyses of 16S rDNA to identify Sodalis and Spiroplasma endosymbionts. The prevalence of both symbionts in field-collected psyllid populations was determined: Sodalis was detected in 100% of field populations, while Spiroplasma was present in 82.5% of individuals. Phylogenetic analysis using 16S rDNA revealed that Sodalis infecting B. trigonica was more closely related to symbionts infecting weevils, stink bugs and tsetse flies than to those from psyllid species. Using fluorescent in situ hybridization and immunostaining, Sodalis was found to be localized inside the nuclei of the midgut cells and bacteriocytes. Spiroplasma was restricted to the cytoplasm of the midgut cells. We further show that a recently reported Bactericera trigonica densovirus (BtDNV), a densovirus infecting B. trigonica was detected in 100% of psyllids and has reduced titers inside CLso-infected psyllids by more than two-fold compared to CLso uninfected psyllids. The findings of this study will help to increase our understanding of psyllid–endosymbiont interactions.